2017
DOI: 10.3390/atoms5020020
|View full text |Cite
|
Sign up to set email alerts
|

Configuration Interaction Effects in Unresolved 5p65dN+1−5p55dN+2+5p65dN5f1 Transition Arrays in Ions Z = 79–92

Abstract: Configuration interaction (CI) effects can greatly influence the way in which extreme ultraviolet (EUV) and soft X-ray (SXR) spectra of heavier ions are dominated by emission from unresolved transition arrays (UTAs), the most intense of which originate from ∆n = 0, 4p 6 4d N+1 −4p 5 4d N+2 +4p 6 4d N 4f 1 transitions. Changing the principle quantum number n, from 4 to 5, changes the origin of the UTA from ∆n = 0, 4p 6 4d N+1 −4p 5 4d N+2 +4p 6 4d N 4f 1 to ∆n = 0, 5p 6 5d N+1 −5p 5 5d N+2 +5p 6 5d N 5f 1 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Liu et al previously showed that the effect of CI on the 5d-5f and 5p-5d emission arrays along the isoelectronic sequence becomes important for 5d-5f beyond Pb 7+ , while the effects of CI on 5p-5d emission only becomes important once these transitions overlap with the 5d-5f array [27]. Overall, they found that CI causes a shift to higher energy and a slight increase in array width.…”
Section: Line Emission In the 10−18 Nm Regionmentioning
confidence: 95%
See 1 more Smart Citation
“…Liu et al previously showed that the effect of CI on the 5d-5f and 5p-5d emission arrays along the isoelectronic sequence becomes important for 5d-5f beyond Pb 7+ , while the effects of CI on 5p-5d emission only becomes important once these transitions overlap with the 5d-5f array [27]. Overall, they found that CI causes a shift to higher energy and a slight increase in array width.…”
Section: Line Emission In the 10−18 Nm Regionmentioning
confidence: 95%
“…Liu et al has identified emission bands in Bi plasmas between 8 nm and 17 nm from 5p-5d, 5d-5f, 5s-5p and 5f-5g transitions in ion stages from Bi 23+ -Bi 35+ [26]. In other related work Liu et al carried out a study to assess the effects of CI on the UTA emission from 5p 6 5d N+1 -5p 5 5d N+2 + 5d N 5f 1 transitions in elements Au to U [27].…”
Section: Atomic Structure Calculationsmentioning
confidence: 99%